2009
DOI: 10.1116/1.3250204
|View full text |Cite
|
Sign up to set email alerts
|

Scanning-helium-ion-beam lithography with hydrogen silsesquioxane resist

Abstract: A scanning-helium-ion-beam microscope is now commercially available. This microscope can be used to perform lithography similar to, but of potentially higher resolution than, scanning electron-beam lithography. This article describes the control of this microscope for lithography via beam steering/blanking electronics and evaluates the high-resolution performance of scanning helium-ion-beam lithography. The authors found that sub-10 nm-half-pitch patterning is feasible. They also measured a point-spread functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
85
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(85 citation statements)
references
References 20 publications
0
85
0
Order By: Relevance
“…A helium ion microscope can also be used for nanofabrication. Sidorkin et al [16] and Winston et al [17] demonstrated the high-resolution manufacturing capabilities of He + beam lithography. Bell et al used an HIM to cut narrow graphene stripes [18].…”
Section: Introductionmentioning
confidence: 99%
“…A helium ion microscope can also be used for nanofabrication. Sidorkin et al [16] and Winston et al [17] demonstrated the high-resolution manufacturing capabilities of He + beam lithography. Bell et al used an HIM to cut narrow graphene stripes [18].…”
Section: Introductionmentioning
confidence: 99%
“…In resist based lithography with light and ions, it has been shown that the PSF can be deduced from spot exposure arrays. 21,22 We can adopt this concept for nanopore milling: When the breakthrough dose is exceeded at a certain point in the PSF, a hole is created. The diameter of a nanopore is therefore related to the width of the PSF at a certain height.…”
mentioning
confidence: 99%
“…HSQ is a high resolution electron beam resist and it permits highresolution SEM inspection following patterning and development. The helium ion beam lithography technology is in its beginnings but it has already demonstrated an ability to fabricate 10 nm hues with a 20 nm pitch [31]. There is still much to be done, but ion beam lithography shows promise and the sensitivity of the resist materials can be substantially higher, so higher -throughput direct lithography may be possible.…”
Section: Helium Ion Beam Lithographymentioning
confidence: 99%